JMC684 : Metalsmithing contemporary design outcome / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2023)
The course prepares the students to produce and present an outstanding portfolio of work comprising original and innovative design solution demonstrating efficiency inappropriate visualization methods, design application, materials, equipment, techniques and processes in a disciplined and responsible way.